(untitled) (Journal of actual problems of jurisprudence, 2018)
Issues of application of measures of criminal procedural correction that differ in special relevance are regarded in the following article. And it is obvious, because the problem solving of all criminal legal proceedings depends on its legitimacy, because the main goal of this compulsion is assisting in solving general process issues. The main aim of this article is to regard transition to adversarial type of process that has conditions which provides with opportunity to avoid abuse from investigative and judicial side and to minimize probability of committing procedural mistakes during the performance of their professional functions, thus only then there can be real compliance of rights and process participants’ freedom. Today, problem of illegal and unsubstantiated arresting retains acute. In criminal process the most restrictive measure, applied to suspect (accused) in committing criminal offense is imprisonment. Exactly that measure mostly limits constitutional rights to freedom and personal inviolability. One of the most serious problem directed to correct appliance of the strictest criminal – procedure preventive measure, in new Criminal Procedure code of The Republic of Kazakhstan, of course, is judicial order of imprisonment. It is important step in realization of reformatory idea turning court of law from crime struggling instrument into human rights agency. In the article also regarded a question that functions of commencement of a motion and its maintaining in court should be in absolute competence of public prosecutor, because only he can represent interests of the country in the court and also he has a function to maintain state accuse. On the other hand, the role of investigator in investigation of criminal case should be minimized and commencement of a motion about preventive measure like imprisonment should not be included in his competence. Key words: procedural preventive measure, preventive measure, pre-trial proceeding, imprisonment, investigative judge, procedural prosecutor, investigator.